Réponses

Meilleure réponse !
2014-05-21T20:35:05+02:00
A) 2x - 2 = 2 
2x = 4
x = 4/2
x=2

B) 3z - 10 = 11
3z = 11 + 10
3z = 21
z = 21/3
z=7

C) 1 -y = 0
-y = -1
y=1

D) 1 + 5x = -39
5x = -39 - 1
5x = -40
x = -40/5
x = -8

E) 2 + 3z = 9
3z = 9-2
3z = 7
z = 7/3

F) 6 -y = -2,3
-y = -2,3 - 6
-y = -8,3
y = 8,3

G) 7 - 3x = -22
-3x = -22 - 7
-3x = -29
x = -29/-3
x= 29/3

H) 5 + 6z = -11
6z = -11 - 5
6z = -16
z = -16/6
z = -8/3 

I) -x - 9 = 11,2
- x = 11,2 + 9
- x = 20,2
x = -20,2

J) 9,7y - 5,7 = -1,7
9,7y = -1,7 + 5,7
9,7y = 4
y = 4/9,7
y= 40/97